Functional roles and metabolic niches in the honey bee gut microbiota. (June 2018) - Bonilla-Rosso, Germán; Engel, Philipp
Highlights: Honey bees harbor a simple gut microbiota that is experimentally tractable. The gut microbiota increases body weight gain and confers pathogen resistance. Fermentation and breakdown of pollen wall components are major metabolic activities. Individual community members have specialized yet overlapping metabolic capacities. Abstract : Gut microbiota studies on diverse animals facilitate our understanding of the general principles governing microbiota–host interactions. The honey bee adds a relevant study system due to the simplicity and experimental tractability of its gut microbiota, but also because bees are important pollinators that suffer from population declines worldwide. The use of gnotobiotic bees combined with genetic tools, 'omics' analysis, and experimental microbiology has recently provided important insights about the impact of the microbiota on bee health and the general functioning of gut ecosystems.